Pengaruh Employer Branding Activity dan Perceived Job Attributes terhadap Intention to Apply - Nurfaizi, Awal; Ikhram , Abdi Dzil (Jurnal Kewirausahaan dan Inovasi, 2024)
The war for talent has made every company in various industries compete and race to acquire the best talent. Manufacturing is the most sought-after industry in the labor market, which means that each company in this industry faces more significant challenges in attracting the best talent in the labor market. This research aims to explain the influence of employer branding activities, consisting of three dimensions (publicity, word of mouth, advertising), and perceived job attributes, consisting of five dimensions (working atmosphere, career opportunities, work-life comfort, task attractiveness, and payment attractiveness) on the intention to apply for a job at PT Nestlé Indonesia. The type of research used in this study is explanatory research with a quantitative approach. The sample consisted of 400 respondents who were students from the University of Brawijaya. The data collection method used was a survey method with the distribution of questionnaires. The testing instruments used in this study include instrument tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis. The results of the study indicate that employer branding activities significantly influence the intention to apply. The results also show that perceived job attributes also significantly influence the intention to apply.   Abstrak War for talent membuat setiap perusahaan di berbagai industri berlomba dan berkompetisi untuk mendapatkan talent terbaik. Manufaktur menjadi industri yang paling diminati di pasar tenaga kerja, sehingga setiap perusahaan dalam industri ini menghadapi tantangan yang lebih besar dalam menarik talenta terbaik di pasar tenaga kerja. Penelitian ini bertujuan untuk menjelaskan pengaruh employer branding activity yang terdiri dari tiga dimensi (publicity, word of mouth, advertising) dan perceived job attributes yang terdiri dari lima dimensi (working atmosphere, career opportunities, work-life comfort, task attractiveness, dan payment attractiveness) terhadap intention to apply di PT Nestlé Indonesia. Jenis penelitian yang digunakan adalah penelitian eksplanatori dengan pendekatan kuantitatif. Sampel terdiri dari 400 responden yang merupakan mahasiswa dari Universitas Brawijaya. Metode pengumpulan data yang digunakan adalah metode survei dengan penyebaran kuesioner. Alat uji yang digunakan dalam penelitian ini meliputi uji instrumen, uji asumsi klasik, pengujian hipotesis, dan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa employer branding activity berpengaruh signifikan terhadap niat melamar pekerjaan. Hasil juga menunjukkan bahwa perceived job attributes juga berpengaruh signifikan terhadap intention to apply.